Low-temperature sprayed carbon electrode in modular HTL-free perovskite solar cells: a comparative study on the choice of carbon sources. Issue 10 (18th February 2021) - Chen, Ransheng; Feng, Yulin; Jing, Liu; Wang, Minhuan; Ma, Hongru; Bian, Jiming; Shi, Yantao
Abstract : Among the three carbon sources (MWCNT, CNC, and graphene), MWCNT was identified as the best candidate for application as the back electrode in HTL-free C-PSCs. Ultimately, an improved PCE of 11.2% was achieved for modular MWCNT-based PSCs. Abstract : Due to their outstanding advantages like excellent moisture resistance and compatibility with up-scalable manufacturing processes, carbon (C) electrode hole transport layer (HTL)-free perovskite solar cells (PSCs) represent an excellent solution to the serious limitations caused by the commonly used HTL and expensive noble metal electrode. The C-electrode can be deposited using different techniques from various carbon allotropes and their derivatives. However, the choice of optimal carbon sources is still open to debate, which will certainly have a strong effect on the performance and long-term stability of the resulting PSCs. Here, the modular HTL-free C-PSCs were assembled by the lamination of two independently processed half-stacks of a semi-cell and a charge collector, where the C-electrodes were processed using a simple spray coating technique at low temperature (85 °C). Three typical carbon sources were used, i.e., multiwall carbon nanotube (MWCNT), carbon nanocoil (CNC), and graphene. A comparative study was conducted to determine the best candidate. Results indicated that MWCNT might be more preferable as the back electrode in HTL-free PSCs in terms of well-aligned band alignment, superior ability in extraction and collection of photo-generated holes. As a result, an improved power conversion efficiency (PCE) of 11.2% was achieved for modular MWCNT-based PSCs, and much improved thermal and humidity stabilities were also demonstrated. Our achievement demonstrates the irreplaceable role of tri-functional MWCNT in C-based HTL-free PSCs with integrated function: (i) back electrode; (ii) hole extraction and collection; and (iii) excellent moisture barrier.